The Electric-Thermal Uneven Characteristics Simulation of Wide Mg Alloy Strip and Electroplastic Rolling Experiment - Gengliang Liu; Lipo Yang; Hailong Zhang (Applied Sciences, 2023)
In order to solve the problem of wide magnesium strip uneven deformation in electroplastic rolling, an uneven field measurement device was designed. The device simulates the actual electro-thermal characteristics and provides as even and constant field conditions as possible for high-efficiency wide Mg strip rolling. Firstly, the effect of electrode position and distance on the electric field unevenness of magnesium strip is observed by setting the electric rolling condition, to provide the optimal electrical-thermal field quantity coupling conditions required by electric rolling. Secondly, in order to reveal the changing trend of the transient field in the actual rolling, the three-dimensional electric field of wide magnesium strip are simulated by the finite element method. The results show that the even temperature field and stable stress field required by the EPR of a wide Mg strip can be guaranteed to the greatest extent by setting electric field parameter Online. The case proves that the continuous EPR of Mg strip with a thickness of less than 0.13 mm without heat treatment can be realized by fine control of the EPR process.